Biocellulose-based flexible magnetic paper - Barud, H. S. [UNESP]; Tercjak, A.; Gutierrez, J.; Viali, W. R. [UNESP]; Nunes, E. S. [UNESP]; Ribeiro, S. J. L. [UNESP]; Jafellici, M. [UNESP]; Nalin, M. [UNESP]; Marques, R. F. C. [UNESP] (Amer Inst Physics, 2015)
Biocellulose or bacterial cellulose (BC) is a biocompatible (nano) material produced with a three-dimensional network structure composed of microfibrils having nanometric diameters obtained by the Gluconacetobacter xylinus bacteria. BC membranes present relatively high porosity, allowing the incorporation or synthesis in situ of inorganic nanoparticles for multifunctional applications and have been used as flexible membranes for incorporation of magnetic nanocomposite. In this work, highly stable superparamagnetic iron oxide nanoparticles (SPION), functionalized with polyethylene glycol (PEG), with an average diameter of 5 nm and a saturation magnetization of 41 emu/g at 300K were prepared. PEG-Fe2O3 hybrid was dispersed by mixing a pristine BC membrane in a stable aqueous dispersion of PEG-SPION. The PEG chains at PEG-SPION's surface provide a good permeability and strong affinity between the BC chains and SPION through hydrogen-bonding interactions. PEG-SPION also allow the incorporation of higher content of nanoparticles without compromising the mechanical properties of the nanocomposite. Structural and magnetic properties of the composite have been characterized by XRD, SEM, energy-dispersive X-ray spectroscopy (EDX), magnetization, Raman spectroscopy, and magnetic force microscopy. (C) 2015 AIP Publishing LLC.